Multimodal analgesia as an essential part of enhanced recovery protocols in the ambulatory settings - Kaye, Alan David (J Anaesthesiol Clin Pharmacol, 2019)
Enhanced recovery after surgery protocols are multimodal perioperative care pathways designed to achieve early recovery in patients after surgical procedures by defining and maintaining preoperative organ function and minimizing the profound stress response following surgery. Enhanced recovery protocols have primarily been studied for major abdominal surgeries, however, the knowledge acquired from studying these protocols has facilitated treating patients in ambulatory settings. The key components of enhanced recovery protocols include preoperative counseling, preoperative nutrition, altering the standard perioperative fasting guidelines, and the value of carbohydrate loading up to 2 hours preoperatively, standardized analgesic, and anesthetic regimens (epidural and nonopioid analgesia) and early mobilization. A PubMed search was performed with the following key words: multimodal analgesia, enhanced recovery, ambulatory care, pain management, and opioids. We discuss the use of enhanced recovery protocols and multimodal pain care plans in the ambulatory setting.